Revision of the genus Aspicera Dahlbom, 1842 (Hym.: Figitidae: Aspicerinae) - Ros-Farré, P.; Pujade-Villar, J. (Zootaxa, 2013)
The genus Aspicera Dahlbom (Hymenoptera: Cynipoidea: Figitidae: Aspicerinae) is revised herein. Aspicera has a Holarctic distribution, being here cited for the first time from the following countries: Canada, Cyprus, Greece, India (northeastern corner, which is part of the Himalayan southeastern range and is considered as belonging to the Palaearctic), Japan, Jordan, Mexico, Montenegro, and Turkey. Morphological characters necessary to differentiate the species of Aspicera are described. The 27 previously described species of Aspicera were revised, always studying the type material when available (21 species); the type material of A. aegyptica Hedicke, 1928, A. chlapowskii Kieffer, 1901, A. coriacea Kieffer, 1901, A. lobata Hedicke, 1928, A. sibirica Kieffer, 1901, A. spinosa (Boyer de Fonscolombe, 1832) are lost or destroyed, these species were studied with the original descriptions. Of the 27 known species, 16 are considered as valid and are redescribed; A. effincta Belizin, 1952 is syn. nov. of A. suecica Dalla Torre & Kieffer, 1910, and A. brevispina Kieffer, 1901 and A. coriacia Kieffer, 1901 are syn. nov. of A. hartigi Dalla Torre, 1889. Aspicera nigra Ionescu, 1969, A. nigricornis Kirby, 1889 and A. rugosa (Hartig, 1843) do not belong to the Aspicerinae, but respectively to the genera Xyalophora and Neralsia (Figitinae), and Xyalaspis (Anacharitinae): Xyalophora nigra (Ionescu) n. comb., Neralsia nigricornis (Kirby) n. comb. and Xyalaspis rugosa Hartig status restored. Aspicera lobata Hedicke, 1928 is considered as ‘incertae sedis’. The examination of additional specimens suggests that there is a general lack of knowledge of the species diversity of this genus. Thirty two new species are described: A. adelae Ros-Farré n. sp., A. annae Ros-Farré & Pujade-Villar n. sp., A. belizini Ros-Farré & Pujade-Villar n. sp., A. blancae Ros-Farré n. sp., A. buffingtoni Ros-Farré & Pujade-Villar n. sp., A. caminali Ros-Farré n. sp., A. carinata Ros-Farré & Pujade-Villar n. sp., A. dianae Ros-Farré n. sp., A. kovalevi Ros-Farré & Pujade-Villar n. sp., A. elisendae Ros-Farré n. sp., A. forshzarai Pujade-Villar & Ros-Farré n. sp., A. gemmae Ros-Farré & Pujade-Villar n. sp., A. jantonii Ros-Farré n. sp., A. julii Ros-Farré & Pujade-Villar n. sp., A. kiefferi Ros-Farré & Pujade-Villar n. sp., A. magdae Ros-Farré & Pujade-Villar n. sp., A. marginata Ros-Farré & Pujade-Villar n. sp., A. martae Ros-Farré & Pujade-Villar n. sp., A. danielssoni Ros-Farré & Pujade-Villar n. sp., A. carlestolrai Ros-Farré & Pujade-Villar n. sp., A. mireiae Ros-Farré & Pujade-Villar n. sp., A. porif Ros-Farré n. sp., A. marginata Ros-Farré & Pujade-Villar n. sp., A. punctifrons Ros-Farré & Pujade-Villar n. sp., A. readae Ros-Farré & Pujade-Villar n. sp., A. robusta Ros-Farré & Pujade-Villar n. sp., A. santamariai Ros-Farré & Pujade-Villar n. sp., A. sergioi Ros-Farré n. sp., A. singularica Ros-Farré & Pujade-Villar n. sp., A. teresae Ros-Farré n. sp., A. tomasi Ros-Farré n. sp., A. zuparcoi Ros-Farré & Pujade-Villar n. sp. A key to all 48 valid species of Aspicera is given. All species are illustrated.